The p48 flow diverter: First clinical results in 25 aneurysms in three centers. Issue 3 (June 2021) - den Bergh, FRA Van; De Beule, T; van Rooij, WJ; Voormolen, MH; Van der Zijden, T; Stockx, L; van Zwam, WH; Fransen, H
Background: The novel low-profile p48 flow diverter has been designed to treat aneurysms on small vessels of 1.75–3mm. We report our first clinical experiences. Methods: Between March 2018–January 2020, 22 patients with 25 aneurysms were treated with the p48 in 3 centers. One patient had 3 aneurysms covered by one p48 and one patient had 2 aneurysms. There were 5 men, 17 women, with a mean age of 55 years (median 59, range 29–73 years). Results: In 25 aneurysms, 24 p48 flow diverters were placed. In 1 patient additional coils were placed in the aneurysm. Procedural vessel rupture by the micro guidewire occurred in 2 patients and vessel rupture during p48 balloon dilatation occurred in 1 patient. Overall, the permanent morbidity rate was 13.6% (3 of 22, 95%CI 3.9–34.2%) and mortality was 4.5% (1 of 22, 95%CI <0.01–23.5%). Most complications were procedure-related and not device-specific. Of 22 patients with 25 aneurysms treated with p48, 18 patients with 20 aneurysms had angiographic follow-up after 5–18 months. Of 19 aneurysms, 10 were occluded and 7 showed a remnant. Two aneurysms were open after 6 months. Three aneurysms were still not occluded after 12, 14, and 18 months and these 3 were retreated. Retreatment rate was 16% (3 of 19) and the adequate occlusion rate was 90% (17 of 19). Conclusions: Treatment of aneurysms in small-caliber vessels with the p48 is feasible and effective but is not without complications. More data is needed to establish indications, safety, and efficacy more accurately.